2011
DOI: 10.1039/c1cc11870f
|View full text |Cite
|
Sign up to set email alerts
|

On the utility of S-mesitylsulfinimines for the stereoselective synthesis of chiral amines and aziridines

Abstract: The synthetic utility of S-mesitylsulfinimines for the synthesis of chiral amines and aziridines was examined through their reactions with Grignard reagents, with the ylides derived from trimethylsulfonium iodide and S-allyl-tetrahydrothiophenium bromide and through an aza-Darzens manifold, affording convenient access to a diverse range of highly substituted chiral amines and aziridines in high yields and excellent stereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…There are chiral N-phosphinyl imines 2f1 , 2f2 [ 60 , 61 ] and chiral sulfimines 2f3 , 2f4 [ 62 , 63 , 64 ] presented ( Scheme 13 ). N-phosphinyl imines 2f1 have been successfully used in aza -Darzen reaction with enolates generated from esters 15b in ten examples of aziridines cis - 1a7 in 72–82% chemical yields and >80% de [ 60 ].…”
Section: Aziridination Of Imines (Path A)mentioning
confidence: 99%
See 3 more Smart Citations
“…There are chiral N-phosphinyl imines 2f1 , 2f2 [ 60 , 61 ] and chiral sulfimines 2f3 , 2f4 [ 62 , 63 , 64 ] presented ( Scheme 13 ). N-phosphinyl imines 2f1 have been successfully used in aza -Darzen reaction with enolates generated from esters 15b in ten examples of aziridines cis - 1a7 in 72–82% chemical yields and >80% de [ 60 ].…”
Section: Aziridination Of Imines (Path A)mentioning
confidence: 99%
“…Corresponding 3-aryl and 3.3-diaryl products were obtained in moderately good cis -selectivity (71:29–98:2); eight examples of 3-aryl products cis - 1a7 were demonstrated. Isolated examples of S-mesitylsulfinyl imines 2f4 have been employed in aziridine cis - 1a7 synthesis [ 63 ]. Trisubstituted 3-aryl aziridine-2-carboxylates cis - 1a7 were obtained from substituted 2-bromoesters 15b and tert -butane sulfinyl aldimines 2f3 [ 64 ] in >60% chemical yields and >98% de (five examples).…”
Section: Aziridination Of Imines (Path A)mentioning
confidence: 99%
See 2 more Smart Citations
“…Initially introduced by Davis, 11 we have found that they offer selectivity near that of the hindered tert-butanesulfinimines, but offer complementary reactivity in Grignard additions, giving high diastereoselectivities in an open-transition state addition. 12 Furthermore, the mesityl group can be more easily removed, which can be useful for particularly sensitive substrates such as N-sulfinyl aziridines. 10,11 We recently reported a convenient one-pot procedure for the synthesis of mesitylsulfinimines in >99% ee using a phenyl alanine-based template, 13 and thus they are also readily available substrates.…”
mentioning
confidence: 99%